ALIRAN FILSAFAT PROGRESIVISME DAN KAITANNYA DENGAN PENDIDIKAN INKLUSI UNTUK ANAK BERKEBUTUHAN KHUSUS - Idawati, Idawati; Sehu, Hijrawati; Sunarti, Trye (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
Progressivism emphasizes experience-based learning and individual development, including for Children with Special Needs (CSN). CSN face physical, mental-intellectual, social, and emotional challenges that affect their development compared to other children. The Indonesian government has ensured inclusive education to help CSN reach their full potential. This study aims to analyze the relationship between progressivism and inclusive education for CSN. The research employs a literature review method by examining books, scientific journals, and related articles. Data is analyzed through reduction, presentation, verification, and conclusion drawing to understand the implementation of progressivism in inclusive education. Findings indicate that the role of teachers, curriculum, classroom management, assessment methods, and accessibility are key factors in supporting progressivism-based inclusive education. Applying these principles creates a more adaptive and student-centered learning environment. In conclusion, integrating progressivism into inclusive education has the potential to strengthen Indonesia’s education system towards greater inclusivity. Optimal implementation will support the achievement of national education goals that ensure equity for all students.